Analisis Pengaruh Positioning, Diferensiasi Dan EkuitasMerek Terhadap Keputusan Pembelian Pada ProdukKuku Bima Ener-G (Studi Pada Pelanggan Toko H.Abas Kelurahan Semanan, Kecamatan Kalideres) - Mayliana, Mayliana; Febriansyah, Febriansyah (Benefit, 2013)
At the present time, industrial business are facing the situation of increasingly intense competition, the emergence of competition beetween brand of the old with the emergence of new brand at the same products. Therefor, a better understanding of consumer behavior is needed to maintain by the company.This resaerch aim to find out of the influence of positioning, differentiation and brand equity to the consumer decision order to purchase energy drink of kuku bima ener â g. UsingÂ  the purposive sampling technique 100 respondents were obtained and become the sampel for this research. Data was analyze by using quantativeÂ  analyze which focused on multiple regresion.The result show, all variabel of independent has a direct corelation with the dependent variabel. Coeficient of determination show in the adjusted squre 85.9%Â  which mean that is influence purchasing decision can be explained by three independent variabel in this research. And remaining 14,1%Â  can be explained by other variables outside the model of the research.Â